The Low Cycle Fatigue Behaviour of Laser Powder Bed Fused Stainless Steel 316LN: Build Orientation and Surface Finish Effects - WILLIAM BEARD (2023)
Additive manufacturing (AM) is a rapidly growing technology which is extending its influence into many industrial sectors such as aerospace, automotive and marine. Recently the nuclear sector has considered AM in the production of nuclear reactor components due to its possible advantages over conventional manufacturing routes. This includes considerable cost savings due to less material wastage, the ability to produce complex near net shape components that conventional manufacturing processes are unable to achieve and a reduced manufacturing time. Initially, Stainless Steel 316LN (SS316LN) manufactured by Laser Powder Bed Fusion (LPBF) has been identified as a potential candidate. However, there are multiple engineering challenges and questions associated with the introduction of LPBF parts into safety critical applications relating to the inherent processing defects, transient nature of the microstructure and rough surface finish which affect the subsequent mechanical behaviour of LPBF components. One of the main factors influencing a component’s cyclic performance is the surface finish. As-built LPBF parts exhibit a rough surface finish due to the layer-by-layer nature of the AM process, which will in turn typically hinder the cyclic response of the component. This behaviour is further influenced by the build orientation of the AM component, with alternative orientations providing a different surface profile alongside a contrasting microstructural morphology. Therefore, alternative finishing methods have been explored to maximise the component’s fatigue performance whilst also considering cost and time. This study will first explore the Low Cycle Fatigue (LCF) behaviour of LPBF SS316LN built in three principal build orientations (vertical (90°), horizontal (0°) and diagonal (45°)) subjected to a conventional polishing procedure to identify the effects of build orientation on the mechanical performance. In addition to this, the LCF behaviour of LPBF SS316LN built in two principal directions (vertical (90°) and diagonal (45°)) with several post-manufacture finishing processes will be assessed to identify the optimal finish for mechanical performance. The LCF results are supported by various microstructural, fractographic and advanced surface profilometry assessments.The LCF results alongside various microstructural, fractographic and advanced surface profilometry findings have revealed that surface roughness alone can not be considered to be the controlling influence on LCF behaviour. An as-built surface finish will inherently provide a greater number of surface breaking stress raisers, however, a novel Rösler mass finishing polishing procedure has been found to produce a similar effective stress concentration factor compared to conventional longitudinal polishing, offering a more viable and less time consuming alternative. Several other key factors must also be considered when assessing the fatigue performance of LPBF built materials, including build direction and the resulting grain orientation, density of the additive structure and the material’s sensitivity to the presence of notched features at the surface. The LCF build orientation results revealed that the vertical (90°) orientation displayed the longest fatigue lives whilst the diagonal (45°) material displayed the shortest lives. Finally, the generated mechanical data has also been interpreted through empirical modelling, and the various data sets have been successfully correlated to enable fatigue life predictions outside the testing regimes.